Knowledge-based services: today and tomorrow - Marina Doroshenko (Foresight and STI Governance)
The study of knowledge-based services sector conducted by the author is in line with pioneering areas of scientific development because this sector was formed relatively recently. The tradition of its separate consideration has emerged in the context of studies of post-industrial society.